Comparative Evaluation Of The Effectiveness Of Interventional Treatment Of Patients With Myocardial Infarction Based On Data Of Ternopil Region - Terenda, N. O.; Petrashyk, Yu. M. (Hospital Surgery. Journal named by L.Ya. Kovalchuk, 2017)
The aim of the work: to determine the effectiveness of medical coronary artery stenting in patients with myocardial infarction (MI). Materials and Methods. The study used data from medical records of 278 in-patients with MI who were hospitalized in the Ternopil City Community Hospital (TCCH) No2. Methods used: data copying, statistical and analytical methods. Results and Discussion. For the study of effectiveness of cardiology interventions, two groups of patients were selected. The first group consisted of 173 patients diagnosed with myocardial infarction who underwent urgent coronary angiography and stenting of coronary arteries (SCA) with balloon angioplasty. The second group consisted of patients diagnosed with myocardial infarction (94) who underwent conventional treatment. This examined the localization and depth of the heart muscle lesions, and clinical manifestations. Hypertension was revealed in patients in the first and second groups in 75.1 % and 84.0 % of cases respectively and type II diabetes in 19.1 % and 33.0 % respectively. The average length of stay of a hospitalized patient in the first group was significantly lower – 12.0 ± 0.17 b/d – than in the second group of patients – 12.9±0.29 b/d. The study also found a significant increase in motor activity in patients with interventional therapy (878.6 ±53.33 m and 591.5 ±34.67 m respectively). Patients with myocardial infarction who underwent SCA, unlike patients with MI who received conventional treatment, showed the best indicators of medical care efficiency. Thus, significantly lower average length of stay of a hospitalized patient at significantly greater motor mode expansion was observed.